Предмет: Алгебра,
автор: izabel12
Помоги пожалуйста упростить
Приложения:
Ответы
Автор ответа:
0
1)1/(x+y)-x/[y(x+y)]=(y-x)/[y(x+y)]
2)y²/[x(x-y)(x+y)]-y/[x(x-y)]=(y²-xy-y²)/[x(x-y)(x+y)]=-xy/[x(x-y)(x+y)]=
=y/[(y-x)(x+y)]
3)(y-x)/[y(x+y)]*y/[(y-x)(x+y)]=1/(x+y)²
2)y²/[x(x-y)(x+y)]-y/[x(x-y)]=(y²-xy-y²)/[x(x-y)(x+y)]=-xy/[x(x-y)(x+y)]=
=y/[(y-x)(x+y)]
3)(y-x)/[y(x+y)]*y/[(y-x)(x+y)]=1/(x+y)²
Похожие вопросы
Предмет: Английский язык,
автор: trhjrtjrtj
Предмет: Биология,
автор: djdjbsnsjskd
Предмет: Химия,
автор: pitchpie9797
Предмет: Математика,
автор: fainakarpovak
Предмет: Химия,
автор: anastasiyatanc